2019
DOI: 10.3390/medicina55100658
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes in Advanced Maternal Age Delivering Women. Clinical Review and Medico-Legal Issues

Abstract: Background and objecives: Adverse cardiovascular outcomes during pregnancy have increased over the past few decades, with increased numbers of women delivering later in their reproductive life. Other factors include higher rates of female obesity, diabetes, hypertension, cardiovascular diseases and assisted reproductive technology, which has extended fertility. Those at risk require extensive prenatal maternal screening, constant pregnancy supervising, monitoring during labor, delivery and puerperium and caref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…With the increase of maternal age, it is more likely that women present complications during pregnancy [ 34 , 35 ]. Advanced maternal age has been also associated with other pregnancy outcomes such as preterm delivery [ 36 , 37 , 38 ], low birth weight, perinatal death, and cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of maternal age, it is more likely that women present complications during pregnancy [ 34 , 35 ]. Advanced maternal age has been also associated with other pregnancy outcomes such as preterm delivery [ 36 , 37 , 38 ], low birth weight, perinatal death, and cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors have been identified as affecting CVD-related maternal mortality. These include race, advanced maternal age, hypertension, diabetes, obesity, geographic region, income, education level, and type of insurance [ 6 , 10 , 11 ]. Black women have been shown to be at a significant risk of not only CVD-related maternal mortality but also all-cause maternal mortality [ 3 ].…”
Section: Risk Factors Including Racial Geographic and Socioeconomic D...mentioning
confidence: 99%
“…Additionally, this universal screening tool would improve access to healthcare for pregnant women especially at a lower socioeconomic status and reduce the percentage of misdiagnoses and delay in treatment of CVD. In turn, early diagnosis and treatment of CVD has the potential to reduce healthcare costs in addition to significantly affect maternal mortality and morbidity in the United States [ 10 ]. One study evaluating the cost-effectiveness of cardiovascular screening performed by Smith et al out of Colorado demonstrated a screening tool in combination with community health workers reaching out to individuals to implement interventions resulted in a 0.8% reduction in Framingham risk score in the general population and a 2.0% reduction in an at-risk population.…”
Section: Universal Cardiovascular Risk Assessment In Pregnancy and Po...mentioning
confidence: 99%
“…For example, AMA is associated with increased risk of gestational diabetes mellitus, placenta previa, and postpartum hemorrhage 7 . In addition, several adverse cardiovascular phenomena have been associated with AMA, including higher risk of developing hypertension and arrhythmias during pregnancy 10 . These conditions are clinically significant considering that 26% of pregnancy-related deaths between 2006 and 2013 had cardiovascular etiologies 10, 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several adverse cardiovascular phenomena have been associated with AMA, including higher risk of developing hypertension and arrhythmias during pregnancy 10 . These conditions are clinically significant considering that 26% of pregnancy-related deaths between 2006 and 2013 had cardiovascular etiologies 10, 11 . Hypertension during pregnancy can also be used to predict future changes for both mother and fetus; women diagnosed with pregnancy-related hypertension experience a 2-8 fold increase in risk for future hypertension, 1217 while babies born to hypertensive mothers are more likely to develop cardiovascular disease themselves 1821 .…”
Section: Introductionmentioning
confidence: 99%